The child’s voice in praxiological transformation - Mesquita, Cristina (2012)
This study investigates the process of praxiological transformation developed in an early childhood institution. The main objectives of the study were defined around the reconstruction of children’s and educators’ images, hoping to create democratic participatory understandings of central actors that will develop a situated pedagogy of respect and learning (Oliveira-Formosinho, 2009). It undertakes deep dialogues with Childhood Association pedagogical approach for children learning and teachers’ development (Formosinho and Oliveira-Formosinho, 2008) as well as with Effective Early Learning Project (Bertram and Pascal, 2004) as reference for monitoring and evaluating quality coconstruction. This study is located in the qualitative paradigm (Guba and Linkoln, 2005; Dezin and Linkoln, 2006) and is being conducted through a single case study (Stake, 2005, 2007) in the context of an action-research process. The learning process were develop into a collaborative action that puts practitioners as subjects of the research and as participants, in a cooperative process of pedagogical mediation.This learning led the participants to reflect on the ethical issues involving its use. This has been a long and complex process that has had positive effects in the transformation of practices (staff development) and on children learning and participation. The reconceptualization of the image of the child has been key for their right to participate and a professional motivation for educators to change practices.